Das Problem der Einsamkeit in den Romanen von Marlen Haushofer - Palmer, Katarzyna (Studia Germanica Posnaniensia, 2018)
In the beginning the article defines the philosophical, psychological and sociological aspects of the problems of loneliness in modern literature. The author refers here, among other things, to Kierkegaard's, Schopenhauer's, Heidegger's and Jasper's theses showing their reception in l. Bachman's, Th. Bernhard's and P. Handke's works. In the main part the author characterizes figures of women in the main novels of the Austrian writer Marlen Haushofer, proving that all of them are in private, professional and social life lonely figures. In the conclusion the author says that the category of loneliness is a fundamental world-view structure in the w hole writing of Haushofer.